Design of the drive system for an explorer robot with a continuous track traction system - Marco Amaya-Pinos; Mateo Torres-Espinoza; Joan Uruchima-Castro; Castro Julio Loja-Quezada; Luis M. López-López (Advances in Mechanical Engineering)
Exploration robots face a challenge in maintaining stability when traversing uneven surfaces. This article aims to address this issue by proposing the design of a drive system that enables an exploration robot to adapt to terrain irregularities and achieve greater traction capability. The design parameters for the robot’s desired operation are established. Subsequently, the design of the drive system is proposed, consisting of three subsystems: the suspension system, the traction system, and the transmission system. To ensure that the proposed design functions properly under the desired parameters, an analysis is conducted using finite element methods. The resulting analysis provides the stresses, deformations, and safety factors of the components that make up the drive system. Overall, the analyzed components exhibit minimal deformations, which remain within the elastic range, as the yield strength of the materials from which they are made is not exceeded. This article concludes that the proposed design operates reliably under the stresses it must withstand and that a drive system capable of adapting to surface irregularities is essential, as it enhances the mobility of exploration robots.